Assessment instruments used for self-report of pain in hospitalized stroke patients with communication problems: a scoping review - Mandysova, Petra; Klugarová, Jitka; Matějková, Iryna; de Vries, Neeltje J Carolien; Klugar, Miloslav (JBI evidence synthesis, 2022)
OBJECTIVE: The objective of this scoping review was to identify assessment instruments used for the self-report of pain by hospitalized patients who have had a stroke and who have communication problems. INTRODUCTION: Pain assessment in various patient groups has received considerable attention, and a variety of pain assessment instruments exists. Nevertheless, there is a lack of consensus regarding which pain assessment instruments are used for self-report of pain in stroke patients with communication problems. INCLUSION CRITERIA: This review included articles that focused on hospitalized adults who have had a stroke, have communication problems attributable to a stroke, and describe the use of an assessment instrument for the self-report of pain. The scoping review considered systematic reviews, quantitative and qualitative studies, and mixed method studies. METHODS: Ten databases were searched from inception to August 2020, using Embase as the key information source (it yielded 424 papers). Hand-searching of the references of the included articles yielded an additional 12 papers. Papers written in any language were considered. A data extraction table was created to record relevant information in line with the goals and results of each article, the sample studied, and the pain assessment instrument used. RESULTS: Ten papers were included in the review, most of which were descriptive studies. Most papers were from the United Kingdom and the United States. The most common communication problem in stroke patients was aphasia. The participants received care in various hospital settings (eg, rehabilitation units, comprehensive stroke units, palliative care). Eleven assessment instruments were identified. In most cases, the assessment instruments focused on assessing pain presence and pain intensity. The most frequently used unidimensional pain intensity instrument was the numerical rating scale. Four instruments were multidimensional, of which two assessed health-related quality of life, including pain. The most thorough pain assessment instrument was the ShoulderQ, which contains 10 verbal questions and three visual vertical graphic rating scales that focus on the assessment of stroke-related shoulder pain. CONCLUSIONS: A range of both unidimensional and multidimensional self-report pain instruments was identified; however, of all the possible communication problems, most studies focused solely on patients with mild to moderate aphasia. Therefore, further research is recommended, including studies that also enroll patients with various stroke-related communication problems other than aphasia. In addition, the instruments should be translated for research in non-Western countries. Finally, apart from descriptive studies, experimental research with a robust randomized controlled trial design is needed to examine the effect of pain-inducing procedures on the perceived pain in patients with stroke-related communication problems.
Keywords: cévní mozková příhoda; dospělí; Communication; komunikace; Pain; bolest; kvalita života; lidé; afázie; zpráva o sobě; Self Report; Aphasia; Stroke; Quality of Life; Adult; Humans